2022
DOI: 10.3233/adr-220020
|View full text |Cite
|
Sign up to set email alerts
|

Mild Cognitive Disorder in Post-COVID-19 Syndrome: A Retrospective Cohort Study of 67,000 Primary Care Post-COVID Patients

Abstract: Background: Little is known about the impact of COVID-19 on mild cognitive disorder. Objective: The aim of this retrospective cohort study was to investigate whether COVID-19 diagnosis is associated with subsequent mild cognitive disorder (MCD) compared to acute upper respiratory infections (AURI). Methods: This retrospective cohort study used data from the Disease Analyzer database (IQVIA) and included 67,046 patients with first-time symptomatic or asymptomatic COVID-19 diagnoses in 1,172 general practices in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“… Study Country Data source Index time for SARS-CoV-2 infections Study design N Mean/ median follow-up, range If not reported, maximum range of FU? Care type/setting for SARS-CoV-2 infected cases Age range (years) % Female % Hospitalized % in ICU Comparator timing Test status of comparator group Outcomes Abel 2021 [ 32 ] United Kingdom Clinical Practice Research Datalink Aurum Feb 2020 to Dec 2020 Retrospective cohort N = 11,923,105 Median (IQR) – 6.3 (4.0–9.3) weeks Outpatient 16–80+ 50% NA Concurrent No confirmed/ suspected SARS-CoV-2 infection Mental disorders (anxiety disorders, depression, psychosis) Ayoubkhani 2021 [ 33 ] United Kingdom Hospital Episode Statistics Admitted Patient Care and General Practice Extraction Service Data for Pandemic Planning and Research Jan 2020 to Aug 2020 Retrospective cohort N = 95,560 Cov: Mean (SD) – 140 (50) days Con: Mean (SD) – 153 (33) days Inpatient 0–70 + 45% 100 NR Concurrent No confirmed/ suspected SARS-CoV-2 infection Cardiovascular disease (composite of arrhythmia, heart failure, myocardial infarction, and stroke); Chronic kidney disease (dialysis and kidney transplant); Diabetes (type 1 & type 2); Respiratory disorders Bohlken 2022 [ 34 ] Germany IQVIA Disease Analyzer database Mar 2020 to Sept 2021 Retrospective cohort N = 134,092 Cov: Mean – 158 days Con: Mean – 165 days Outpatient 18–70+ 53.3% NA Concurrent >90% had test negative Neurological conditions (mild cognitive disorder) …”
Section: Resultsmentioning
confidence: 99%
“… Study Country Data source Index time for SARS-CoV-2 infections Study design N Mean/ median follow-up, range If not reported, maximum range of FU? Care type/setting for SARS-CoV-2 infected cases Age range (years) % Female % Hospitalized % in ICU Comparator timing Test status of comparator group Outcomes Abel 2021 [ 32 ] United Kingdom Clinical Practice Research Datalink Aurum Feb 2020 to Dec 2020 Retrospective cohort N = 11,923,105 Median (IQR) – 6.3 (4.0–9.3) weeks Outpatient 16–80+ 50% NA Concurrent No confirmed/ suspected SARS-CoV-2 infection Mental disorders (anxiety disorders, depression, psychosis) Ayoubkhani 2021 [ 33 ] United Kingdom Hospital Episode Statistics Admitted Patient Care and General Practice Extraction Service Data for Pandemic Planning and Research Jan 2020 to Aug 2020 Retrospective cohort N = 95,560 Cov: Mean (SD) – 140 (50) days Con: Mean (SD) – 153 (33) days Inpatient 0–70 + 45% 100 NR Concurrent No confirmed/ suspected SARS-CoV-2 infection Cardiovascular disease (composite of arrhythmia, heart failure, myocardial infarction, and stroke); Chronic kidney disease (dialysis and kidney transplant); Diabetes (type 1 & type 2); Respiratory disorders Bohlken 2022 [ 34 ] Germany IQVIA Disease Analyzer database Mar 2020 to Sept 2021 Retrospective cohort N = 134,092 Cov: Mean – 158 days Con: Mean – 165 days Outpatient 18–70+ 53.3% NA Concurrent >90% had test negative Neurological conditions (mild cognitive disorder) …”
Section: Resultsmentioning
confidence: 99%
“…Patients with severe COVID-19 have been found to have transcriptomic changes in their prefrontal cortex like those of older individuals, [28] and severe COVID-19 yielded a drop in global cognitive performance consistent with decline usually spread over 10 years of normal aging, [29] consistent with the results of our study. According to a large cohort study in a primary care setting, when compared to patients with the diagnosis of acute upper respiratory tract infections (AURI), individuals with the diagnosis of COVID-19 had a significantly higher incidence of mild cognitive disorder (7.6 COVID-19 cases/1,000 person-years vs. 5.1 AURI cases/1,000 person-years), but a lower overall incidence [30] indicating that COVID-19 diagnosed outside of general practice may be misclassified as AURI. This limitation may lower the incidence of COVID-19-related MCI.…”
Section: Discussionmentioning
confidence: 99%
“…Erste Hinweise gibt es auch, wie sich die Rahmenbedingungen von hausärztlicher Tätigkeit in Heimen strukturell geändert haben und Folgen für die Patientenversorung aufweisen [14]. In einer eigenen Studie konnten wir zeigen, dass die kognitiven Störungen im Rahmen einer COVID-19-Erkrankung zunahmen, aber dass dies im Praxisalltag ein sehr seltenes Ereignis darstellte [15].…”
Section: Methodenunclassified